A polyether-modified lignin-based porous carbon material and a preparation method and application thereof

CN123002839APending Publication Date: 2026-10-30WUHAN INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611399554.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0007]本发明旨在提供一种利用聚醚修饰木质素制备多孔碳材料的制备方法及其在超级电容器储能中的应用,以解决现有技术中木质素反应活性低、炭化过程中易缩合碳化不均以及难以形成发达孔隙结构等问题

Benefits of technology

本发明利用聚醚对木质素进行温和改性,并结合高温一步炭化工艺,成功制备出聚醚修饰的木质素基多孔碳材料,并将其应用于制备超级电容器电极材料中。与现有技术相比,本发明具有以下优点和积极效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002839A_ABST
    Figure CN123002839A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing porous carbon materials by using polyether modified lignin and for supercapacitor electrode materials. In view of the problems of strong intermolecular crosslinking, insufficient pore structure development and low specific surface area of the obtained carbon materials in the existing lignin carbonization process, the application introduces a polyether additive in the lignin pretreatment process, realizes the lignin structure regulation and molecular modification through a mild chemical reaction, and promotes the pore structure development in the subsequent carbonization process. Then, the modified lignin is subjected to high-temperature carbonization treatment, and a lignin-based porous carbon material with a high specific surface area is prepared, and is further used for preparing a supercapacitor electrode. The method is simple in process, mild in condition and controllable in process, does not need complex multi-step modification and solvent recovery operation, can effectively improve the pore structure of the lignin-based porous carbon material and improve the electrochemical energy storage performance of the lignin-based porous carbon material, and provides an economic, feasible and application potential technical path for the high-value utilization of lignin resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of high-value utilization of lignin and preparation of porous carbon materials, and specifically relates to a polyether-modified lignin-based porous carbon material, its preparation method and application. Background Technology

[0002] Lignin is the second largest renewable organic polymer resource in nature after cellulose, accounting for 15-30% of the dry weight of lignocellulose biomass. As the only natural polymer rich in aromatic structures, lignin has high carbon content, high aromaticity, good thermal stability, and is abundant and renewable, making it an ideal raw material for replacing fossil carbon sources and realizing the preparation of green carbon materials. With the development of biomass refining and clean energy technologies, how to utilize lignin in a high-value manner and transform it into high-performance functional materials has become one of the key directions in sustainable chemical engineering and new carbon materials research.

[0003] Currently, using lignin as a raw material to prepare porous carbon materials and applying them to supercapacitor electrodes is one of the important ways to utilize lignin for high-value purposes. The abundant aromatic skeleton and oxygen-containing functional groups of lignin give it good carbonization potential. Through chemical activation, physical activation, or template methods, carbon materials with high specific surface area and rich pore structure can be further constructed, showing promising application prospects in the field of supercapacitor electrodes. However, the highly complex structure of natural lignin, with its heterogeneous molecular structure and strong intermolecular hydrogen bonding, results in poor thermoplasticity and low reactivity. During direct carbonization, lignin molecules are prone to cross-linking and uneven carbonization, forming a dense structure that makes it difficult to effectively generate a well-developed porous system. This not only limits the specific surface area and pore size control of porous carbon materials but also reduces their ion transport and charge storage performance in supercapacitors.

[0004] To improve the processing properties and structural controllability of lignin, researchers have proposed various modification strategies, including sulfonation, esterification, hydroxymethylation, etherification, and composite modification. These methods, by introducing new functional groups or flexible segments onto lignin molecules, can improve the solubility, dispersibility, and pyrolysis behavior of lignin to some extent, and promote the development of pore structures during subsequent carbonization. However, existing lignin modification technologies still have certain limitations: on the one hand, traditional modification methods often involve cumbersome reaction steps, high energy consumption, and reliance on expensive and somewhat toxic chemical reagents; on the other hand, existing methods mainly focus on regulating the structure of lignin precursors and intermolecular interactions. Although these methods can improve carbonization uniformity and increase porosity to some extent, their pore-forming ability remains relatively limited, and the resulting carbon materials often fail to simultaneously achieve high specific surface area and a reasonable micro / mesoporous structure. Therefore, regulating the structure of lignin precursors alone is insufficient to fully meet the construction requirements of high-performance porous carbon materials. If the modifier used can not only regulate the molecular structure and interfacial properties of lignin, but also undergo thermal decomposition and participate in pore structure formation during subsequent high-temperature carbonization, it is expected to achieve the synergistic effect of precursor structure regulation and in-situ pore formation through pyrolysis, providing a new technical path for further optimizing the specific surface area, pore volume and pore size distribution of lignin-based porous carbon.

[0005] Polyether molecules contain abundant ether bonds and flexible polyoxyethylene / polyoxypropylene segments, exhibiting numerous ether bonds and flexible chain structures. Their molecular structure holds the potential to modulate intermolecular interactions and interfacial properties within lignin. Furthermore, some polyether materials can undergo thermal decomposition at high temperatures, generating volatile components. Based on this, it is speculated that introducing polyethers into lignin precursors may improve the dispersion and structural uniformity of lignin while simultaneously playing a role in in-situ pore-forming during subsequent carbonization. This would promote the synergistic construction of micropores and mesopores, thereby enhancing their application potential in supercapacitor electrode materials.

[0006] In summary, this invention provides a method for preparing porous carbon materials for supercapacitor electrodes using polyether-modified lignin. By controlling the structure and interfacial properties of the lignin precursor through polyether modification and combining carbonization and activation treatments, a lignin-based porous carbon material with excellent pore structure characteristics suitable for supercapacitor electrodes is prepared. This method provides a new technical approach for the high-value utilization of lignin and the preparation of biomass-based energy storage materials, and also holds promise for expanding the applications of lignin-based porous carbon materials in energy storage, adsorption, and catalysis. Summary of the Invention

[0007] This invention aims to provide a method for preparing porous carbon materials using polyether-modified lignin and its application in supercapacitor energy storage, addressing the problems of low lignin reactivity, uneven carbonization due to condensation during carbonization, and difficulty in forming a well-developed pore structure in existing technologies. By subjecting lignin to mild polyether modification, combined with subsequent carbonization and activation treatments, a lignin-based hierarchical porous carbon material with high specific surface area, reasonable pore size distribution, and good structural stability is prepared. Based on this, electrodes are fabricated using this porous carbon material and further assembled into supercapacitors, resulting in high specific capacitance, good electrochemical performance, and excellent cycle stability.

[0008] To achieve the above objectives, the present invention provides a method for preparing porous carbon materials using polyether-modified lignin, the method comprising the following steps: 1) Polyether modification: Mix lignin raw material with water, add polyether additives and acid or base catalysts to the resulting mixture, stir evenly, heat to 100-180℃ and keep warm, cool down and collect the slurry. 2) Separation of polyether-modified lignin: The slurry obtained in step 1) is mixed with acid water and stirred. The solid precipitate is collected by centrifugation, washed and freeze-dried to obtain polyether-modified lignin. 3) Carbonization and activation: The polyether-modified lignin obtained in step 2) is mixed with KOH and calcined at high temperature in an inert gas atmosphere. The carbonized product is then acid-washed, water-washed and dried to obtain lignin-based porous carbon material.

[0009] Furthermore, the lignin raw material in step 1) is any one or a combination of two of commercial alkali lignin, sulfate lignin, and organic solvent lignin.

[0010] Further, the polyether additive in step 1) is any one or a mixture of two or more of polyethylene glycol, octylphenol polyoxyethylene ether, polyoxyethylene lauryl ether, fatty alcohol polyoxyethylene ether, and polyoxyethylene / polyoxypropylene / polyoxyethylene triblock copolymer.

[0011] Furthermore, in step 1), the acid catalyst is an inorganic acid or an organic acid, wherein the inorganic acid is hydrochloric acid or sulfuric acid, and the organic acid is p-toluenesulfonic acid or oxalic acid; and the base catalyst is sodium hydroxide or potassium hydroxide.

[0012] Further, in step 1), the mass ratio of the lignin raw material to water is 1:5 to 1:20; based on the mass of the mixture of lignin raw material and water, the amount of the polyether additive is 0.1 to 1.0%, and the amount of the acid catalyst or alkali catalyst is 0.5 to 3.0%; the heat preservation time is 20 to 120 min.

[0013] Furthermore, in step 3), the mass ratio of the polyether-modified lignin to KOH is 1:1 to 1:6; the heating rate of the high-temperature calcination is 5 to 10 °C / min, the calcination temperature is 650 to 1000 °C, and the holding time is 30 to 120 min.

[0014] Furthermore, in step 3), the acid washing is performed by neutralizing and washing with hydrochloric acid until the filtrate is neutral.

[0015] The present invention also provides a lignin-based porous carbon material, which is prepared by the above method.

[0016] Furthermore, the specific surface area of ​​the lignin-based porous carbon material is 2000–4000 m². 2 / g, pore volume 1.0–3 cm³ 3 / g.

[0017] The present invention also provides a method for preparing a supercapacitor electrode material, comprising: uniformly mixing the above-mentioned lignin-based porous carbon material with acetylene black and polytetrafluoroethylene in N-methyl-2-pyrrolidone to obtain a slurry; coating the slurry onto a current collector; vacuum drying to remove the solvent; and then compacting it under a pressure of 2 to 10 MPa to obtain the supercapacitor electrode material.

[0018] Beneficial effects of this invention: This invention utilizes polyether to mildly modify lignin and combines it with a high-temperature one-step carbonization process to successfully prepare polyether-modified lignin-based porous carbon materials, which are then applied to the preparation of supercapacitor electrode materials. Compared with existing technologies, this invention has the following advantages and positive effects: 1. High resource utilization and low cost. This invention uses inexpensive and renewable lignin as a carbon source. The preparation process is simple, the reaction conditions are mild, and it is suitable for large-scale production and industrial promotion. The polyether additives used are widely available and inexpensive, and have good environmental protection, renewability, and biodegradability. The polyether modification pretreatment process proposed in this invention has strong universality and is applicable to various types and sources of lignin raw materials, and is compatible with different processing methods. This method does not require additional steps for complex modification of lignin, the operating conditions are controllable, and the overall process is green, environmentally friendly, energy-efficient, and easy to operate, making it easy to achieve industrial application.

[0019] 2. This modification process is mild and environmentally friendly. This invention introduces a small amount of modifier and catalyst into an aqueous system, achieving flexibility and homogenization of the lignin molecular structure. The entire process requires no expensive organic solvents, the reaction system is safe and controllable, and it has advantages such as simple operation and environmental friendliness.

[0020] 3. Significantly improves the pyrolysis behavior and pore structure formation of lignin. Through the molecular modification of polyethers, the hydrogen bonding between lignin molecules can be effectively weakened, inhibiting lignin cross-linking reactions during carbonization and making the pyrolysis process more uniform and orderly. Simultaneously, the thermal decomposition of polyether segments during high-temperature carbonization can generate a certain in-situ pore-forming effect, promoting the development of the pore structure of lignin-based carbon materials. This improves the specific surface area, pore volume, and structural stability of the resulting porous carbon materials, providing a good foundation for their application in adsorption, energy storage, and catalysis. Attached Figure Description

[0021] Figure 1 This is an image showing the morphology of lignin-based porous carbon.

[0022] Figure 2 The graphs show a comparison of the electrochemical performance of different lignin-based porous carbon materials. (a, d) are cyclic voltammetry (CV) curves at different scan rates; (b, e) are galvanostatic charge-discharge (GCD) curves at different current densities; and (c, f) are electrochemical impedance spectroscopy (EIS) Nyquist curves. Detailed Implementation

[0023] The technical solutions described below will be clearly and completely described with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] The raw materials for this invention are various lignins, all of which can be used in this invention. The following uses commercial alkali lignin as a preferred embodiment to describe the implementation steps of this invention.

[0025] Example 1: 1) Mix 10 g of alkali lignin raw material with 100 g of water. Based on the mass of the raw material and solvent mixture, add 0.6% polyethylene glycol 4000 and 1.0% hydrochloric acid. After stirring evenly, heat the mixture in a reactor to 140°C and keep it at that temperature for 60 min. After cooling, collect the slurry. 2) Mix the slurry obtained in step 1) with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid), stir, then centrifuge (8000 rpm) to obtain lignin solid precipitate, wash three times with deionized water, and finally freeze-dry to obtain polyethylene glycol modified lignin. 3) Take the lignin (2 g) obtained in step 2) and mix it with KOH (8 g) in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 800℃, and the time is 60 min.

[0026] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and stirred continuously to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. See the image for the porous carbon morphology. Figure 1 The specific surface area, pore volume, and pore diameter of porous carbon are shown in Table 1.

[0027] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was uniformly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 2 MPa to obtain the supercapacitor electrode material.

[0028] 6) Electrochemical tests were performed in a three-electrode system. The electrochemical characteristics of this electrode material are shown in [reference needed]. Figure 2 The specific capacitance results are shown in Table 2.

[0029] Example 2: 1) Mix 10 g of lignin raw material with ethanol organic solvent and 100 g of water. Based on the mass of the raw material and solvent mixture, add 0.8% of polyoxyethylene / polyoxypropylene / polyoxyethylene triblock copolymer F-108 and 0.6% of sodium hydroxide. After stirring evenly, heat the mixture in a reactor to 160°C and keep it at that temperature for 45 min. After cooling, collect the slurry. 2) The slurry obtained in step 1) was mixed with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid) and stirred. Then it was centrifuged (8000 rpm) to obtain lignin solid precipitate. The lignin was washed three times with deionized water and finally freeze-dried to obtain lignin modified with polyoxyethylene / polyoxypropylene / polyoxyethylene triblock copolymer F-108. 3) Take the lignin (2 g) obtained in step 2) and KOH (8 g) and mix them in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 1000℃, and the time is 45 min.

[0030] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and stirred continuously to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. See the image for the porous carbon morphology. Figure 1 The specific surface area, pore volume, and pore diameter of porous carbon are shown in Table 1.

[0031] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was uniformly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 2 MPa to obtain the supercapacitor electrode material.

[0032] 6) Electrochemical tests were performed in a three-electrode system. The specific capacitance results of the electrode material are shown in Table 2.

[0033] Example 3: 1) Mix 10 g of alkali lignin raw material with 100 g of water. Based on the mass of the raw material and solvent mixture, add 0.5% polyoxyethylene lauryl ether and 0.8% hydrochloric acid. After stirring evenly, heat the mixture in a reactor to 160°C and keep it at that temperature for 40 min. After cooling, collect the slurry. 2) Mix the slurry obtained in step 1) with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid), stir, then centrifuge (8000 rpm) to obtain lignin solid precipitate, wash three times with deionized water, and finally freeze-dry to obtain polyether modified lignin. 3) Take the lignin (2 g) obtained in step 2) and mix it with KOH (8 g) in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 800℃, and the time is 60 min.

[0034] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and stirred continuously to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. The specific surface area, pore volume, and pore size of the porous carbon are shown in Table 1.

[0035] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was evenly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 8 MPa to obtain the supercapacitor electrode material.

[0036] 6) Electrochemical tests were performed in a three-electrode system. The specific capacitance results of the electrode material are shown in Table 2.

[0037] Example 4: 1) Mix 10 g of alkali lignin raw material with 100 g of water. Based on the mass of the raw material and solvent mixture, add 1% fatty alcohol polyoxyethylene ether and 0.6% sulfuric acid. After stirring evenly, heat the mixture in a reactor to 120°C and keep it at that temperature for 60 min. After cooling, collect the slurry. 2) Mix the slurry obtained in step 1) with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid), stir, then centrifuge (8000 rpm) to obtain lignin solid precipitate, wash three times with deionized water, and finally freeze-dry to obtain lignin modified with fatty alcohol polyoxyethylene ether. 3) Take the lignin (2 g) obtained in step 2) and KOH (8 g) and mix them in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 900℃, and the time is 90 min.

[0038] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and stirred continuously to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. The specific surface area, pore volume, and pore size of the porous carbon are shown in Table 1.

[0039] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was uniformly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 5 MPa to obtain the supercapacitor electrode material.

[0040] 6) Electrochemical tests were performed in a three-electrode system. The specific capacitance results of the electrode material are shown in Table 2.

[0041] Comparative Example 1: 1) Mix 10 g of alkali lignin raw material with 100 g of water. Add 1.0% hydrochloric acid based on the mass of the raw material and solvent mixture. After stirring evenly, heat the mixture in a reactor to 140°C and keep it at that temperature for 60 min. After cooling, collect the slurry. 2) Mix the slurry obtained in step 1) with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid), stir, then centrifuge (8000 rpm) to obtain lignin solid precipitate, wash three times with deionized water, and finally freeze-dry to obtain unmodified lignin. 3) Take the lignin (2 g) obtained in step 2) and mix it with KOH (8 g) in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 800℃, and the time is 60 min.

[0042] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and stirred continuously to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. See the image for the porous carbon morphology. Figure 1 The specific surface area, pore volume, and pore diameter of porous carbon are shown in Table 1.

[0043] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was uniformly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 2 MPa to obtain the supercapacitor electrode material.

[0044] 6) Electrochemical tests were performed in a three-electrode system. The electrochemical characteristics of this electrode material are shown in [reference needed]. Figure 2 The specific capacitance results are shown in Table 2.

[0045] Comparative Example 2: 1) Mix 10 g of lignin raw material with ethanol organic solvent and 100 g of water. Add 0.6% sodium hydroxide based on the mass of the raw material and solvent mixture. After stirring evenly, heat the mixture in a reaction vessel to 160°C and keep it at that temperature for 45 min. After cooling, collect the slurry. 2) Mix the slurry obtained in step 1) with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid), stir, then centrifuge (8000 rpm) to obtain lignin solid precipitate, wash three times with deionized water, and finally freeze-dry to obtain unmodified lignin. 3) Take the lignin (2 g) obtained in step 2) and KOH (8 g) and mix them in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 1000℃, and the time is 45 min.

[0046] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and stirred continuously to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. See the image for the porous carbon morphology. Figure 1 The specific surface area, pore volume, and pore diameter of porous carbon are shown in Table 1.

[0047] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was uniformly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 2 MPa to obtain the supercapacitor electrode material.

[0048] 6) Electrochemical tests were performed in a three-electrode system. The specific capacitance results of the electrode material are shown in Table 2.

[0049] Comparative Example 3: 1) Mix 10 g of alkali lignin raw material with 100 g of water. Add 0.8% hydrochloric acid based on the mass of the raw material and solvent mixture. After stirring evenly, heat the mixture in a reactor to 160°C and keep it at that temperature for 40 min. After cooling, collect the slurry. 2) Mix the slurry obtained in step 1) with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid), stir, then centrifuge (8000 rpm) to obtain lignin solid precipitate, wash three times with deionized water, and finally freeze-dry to obtain unmodified lignin. 3) Take the lignin (2 g) obtained in step 2) and mix it with KOH (8 g) in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 800℃, and the time is 60 min.

[0050] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and stirred continuously to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. The specific surface area, pore volume, and pore size of the porous carbon are shown in Table 1.

[0051] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was evenly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 8 MPa to obtain the supercapacitor electrode material.

[0052] 6) Electrochemical tests were performed in a three-electrode system. The specific capacitance results of the electrode material are shown in Table 2.

[0053] Comparative Example 4: 1) Mix 10 g of alkali lignin raw material with 100 g of water. Add 0.6% sulfuric acid based on the mass of the raw material and solvent mixture. After stirring evenly, heat the mixture in a reaction vessel to 120°C and keep it at that temperature for 60 min. After cooling, collect the slurry. 2) Mix the slurry obtained in step 1) with 10 times the volume of acidic water (pH 2, adjusted with hydrochloric acid), stir, then centrifuge (8000 rpm) to obtain lignin solid precipitate, wash three times with deionized water, and finally freeze-dry to obtain unmodified lignin. 3) Take the lignin (2 g) obtained in step 2) and KOH (8 g) and mix them in a grinding cup, and continue grinding until powdery. Then place the mixture in a crucible, place it in a tube furnace, and equilibrate in an inert gas atmosphere for 30 min. The heating rate during the carbonization process is 5℃ / min, the temperature is 900℃, and the time is 90 min.

[0054] 4) The carbon solid obtained in step 3) was mixed in 6 M hydrochloric acid and continuously stirred to neutralize. The mixture was then placed in a vacuum filter cup and washed with deionized water until neutral. Finally, the solid was dried in a vacuum drying oven (60℃) for 12 h to obtain lignin-based porous carbon material. The specific surface area, pore volume, and pore size of the porous carbon are shown in the figure. Figure 1 See Table 1.

[0055] 5) The above-mentioned lignin-based porous carbon, acetylene black, and polytetrafluoroethylene are mixed at a mass ratio of 8:1:1 in an appropriate amount of N. methyl 2 The mixture was thoroughly mixed with pyrrolidone, and then the slurry was uniformly coated onto the current collector. The solvent was removed by vacuum drying at 80°C for 12 h, and then compacted under a pressure of 5 MPa to obtain the supercapacitor electrode material.

[0056] 6) Electrochemical tests were performed in a three-electrode system. The specific capacitance results of the electrode material are shown in Table 2.

[0057] Table 1. Pore structure of lignin-based porous carbon

[0058] Table 2 Comparison of specific capacitance of different lignin-based porous carbon materials

[0059] From the appendix Figure 1 It is evident that polyether modification significantly affects the morphology, specific surface area, and pore structure of lignin-based porous carbon materials. The porous carbon materials obtained by further carbonization of polyether-modified lignin exhibit a smooth and dense surface with no obvious impurity residue, and a uniform and continuous pore wall structure. This indicates that polyether additives can effectively inhibit coking agglomeration and inorganic impurity coating during carbonization, thereby improving carbonization uniformity and structural integrity. Simultaneously, the introduction of polyether additives helps to form more gasification channels and microporous structures during carbonization, resulting in porous carbon with a higher specific surface area and a richer pore system. Furthermore, as shown in Table 1, the carbon materials prepared by pyrolysis using polyether-modified lignin as a precursor exhibit superior overall pore structure characteristics, and this modification strategy demonstrates good applicability in both acidic and alkaline catalytic systems. The specific surface areas of the carbon materials obtained in Examples 1–4 reached 3354.2, 3055.2, 2565.3, and 3621.9 m², respectively. 2 g -1 All of these were significantly higher than the response ratios of 1949.3, 1843.5, 1732.4, and 2243.6 m. 2 g -1 The pore volume also increased from 1.0–1.7 cm³ in the comparative example. 3 g -1 Increased to 1.3–2.0 cm 3 g -1 The above results demonstrate that polyether modification can effectively promote the formation and development of pore structures during lignin pyrolysis, significantly increase the specific surface area and pore volume of the obtained carbon material, and maintain a suitable pore size distribution, thereby providing a good pore structure basis for electrolyte ion transport and charge storage.

[0060] Depend on Figure 2As shown in Table 2, the porous carbon materials prepared by pyrolysis using polyether-modified lignin as a precursor exhibit significantly higher specific capacitances than the corresponding comparative examples when used as electrodes in supercapacitors. The obtained porous carbon materials possess a well-developed pore structure and a high specific surface area, providing more accessible active interfaces for electrolyte ions. This also helps shorten ion transport paths and improve mass transfer efficiency, thereby enhancing their electrochemical energy storage performance. These results indicate that polyether modification can effectively promote the formation and development of the pore structure in lignin-based carbon materials, increase the specific surface area and pore volume, and further improve the specific capacitance and energy storage performance of the materials.

[0061] In summary, polyethers regulate the pyrolysis and carbonization behavior of lignin during the pretreatment stage, promoting the formation and optimization of pore structures, ultimately endowing porous carbon materials with excellent structural integrity and specific surface area properties. The polyether-assisted pretreatment method proposed in this invention is simple and requires no additional complex steps. The process route provided by this invention not only has a significant performance improvement effect but also offers a feasible technical approach for the green, economical, and efficient utilization of lignin resources, possessing promising application prospects and significant industrialization value.

[0062] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. A method for preparing porous carbon materials using polyether-modified lignin, characterized in that, The method includes the following steps: 1) Polyether modification: Mix lignin raw material with water, add polyether additives and acid or base catalysts to the resulting mixture, stir evenly, heat to 100-180℃ and keep warm, cool down and collect the slurry. 2) Separation of polyether-modified lignin: The slurry obtained in step 1) is mixed with acid water and stirred. The solid precipitate is collected by centrifugation, washed and freeze-dried to obtain polyether-modified lignin. 3) Carbonization and activation: The polyether-modified lignin obtained in step 2) is mixed with KOH and calcined at high temperature in an inert gas atmosphere. The carbonized product is then acid-washed, water-washed and dried to obtain lignin-based porous carbon material.

2. The method according to claim 1, characterized in that, Step 1) The lignin raw material is any one or a combination of two of the following: commercial alkali lignin, sulfate lignin, and organic solvent lignin.

3. The method according to claim 1, characterized in that, Step 1) The polyether additive is any one or a mixture of two or more of polyethylene glycol, octylphenol polyoxyethylene ether, polyoxyethylene lauryl ether, fatty alcohol polyoxyethylene ether, and polyoxyethylene / polyoxypropylene / polyoxyethylene triblock copolymer.

4. The method according to claim 1, characterized in that, Step 1) The acid catalyst is an inorganic acid or an organic acid, the inorganic acid is hydrochloric acid or sulfuric acid, and the organic acid is p-toluenesulfonic acid or oxalic acid; the base catalyst is sodium hydroxide or potassium hydroxide.

5. The method according to claim 1, characterized in that, In step 1), the mass ratio of the lignin raw material to water is 1:5 to 1:20; based on the mass of the mixture of lignin raw material and water, the amount of the polyether additive is 0.1 to 1.0%, and the amount of the acid catalyst or alkali catalyst is 0.5 to 3.0%; the heat preservation time is 20 to 120 min.

6. The method according to claim 1, characterized in that, In step 3), the mass ratio of the polyether-modified lignin to KOH is 1:1 to 1:6; the heating rate of the high-temperature calcination is 5 to 10 °C / min, the calcination temperature is 650 to 1000 °C, and the holding time is 30 to 120 min.

7. The method according to claim 1, characterized in that, In step 3), the acid washing is performed by neutralizing and washing with hydrochloric acid until the filtrate is neutral.

8. A lignin-based porous carbon material, characterized in that, Prepared by the method according to any one of claims 1 to 7.

9. The lignin-based porous carbon material according to claim 8, characterized in that, The lignin-based porous carbon material has a specific surface area of ​​2000–4000 m². 2 / g, pore volume 1.0–3 cm³ 3 / g.

10. A method for preparing a supercapacitor electrode material, characterized in that, include: The lignin-based porous carbon material of claim 8 or 9 is mixed uniformly with acetylene black and polytetrafluoroethylene in N-methyl-2-pyrrolidone to obtain a slurry. The slurry is coated onto a current collector, vacuum dried to remove the solvent, and then compacted under a pressure of 2 to 10 MPa to obtain the supercapacitor electrode material.